Performance analysis of bank Bukopin Syariah Surabaya with the balance scorecard approach - Sukma Asmaning Ayu; Rifa’atul mafthuhah; Rukhul Amin (Institute of Computer Science (IOCS), 2023)
This study aims to determine the performance of Bank Syariah Bukopin with the Balanced Scorecard approach. This type of research used is descriptive quantitative. Data collection techniques were carried out by observation, questionnaires and interviews. The sampling technique for customers uses a probability sample selection technique. The type of method used is purposive sampling. The research was conducted at Bank Bukopin Syariah by taking financial data from 2021 to 2022 to analyze a financial perspective and conduct interviews to analyze internal business process perspectives. Researchers also used questionnaires distributed to customers and employees in sampling to analyze customer perspectives and learning and growth. In this study the variable used was performance measurement with the balanced scorecard which included four aspects, namely financial perspective, customer perspective, growth perspective and learning perspective. Bukopin's Sharia bank performance, namely the financial perspective shows that financial performance can be categorized as unfavorable, this can be seen from the BOPO and FDR results that financial performance has decreased and ROA has increased in 2021 and 2022. The customer perspective concludes that Bukopin Darmo Sharia bank has experienced an increase customers from 2021-2022. Financial performance shows increase and decrease from year to year, customer satisfaction performance shows satisfaction. Likewise employee satisfaction which shows a fairly good value of satisfaction. Internal business process performance also shows good results in innovation processes and services. Based on the results of this study it can be concluded that the Balanced Scorecard is that for improving the company's finances and performance.